Reference range determination for imaging biomarkers: Myocardial T1. Issue 3 (12th February 2019) - Higgins, David M.; Keeble, Claire; Juli, Christoph; Dawson, Dana K.; Waterton, John C.
Abstract : Background: Imaging biomarkers, such as the T1 relaxation time of the myocardium using MRI, can be valuable in cardiac medicine if they are properly validated. Consensus statements recommend that for myocardial T1, each investigator should establish a reference range. Purpose: To describe a statistically valid method for determining and reporting the reference range in each center, which simultaneously minimizes the twin risks of undersampling, leading to a uselessly uncertain range, and oversampling, which exposes volunteers to unnecessary scanning and wastes resources. Study Type: Cohort. Population: In all, 278 normal human subjects without cardiac disease from two cardiac MR centers. Field Strength/Sequence: 1.5 T and 3 T; Modified Look–Locker Inversion recovery sequence. Assessment: The T1 relaxation time was estimated from multiple samples of tissue magnetization after inversion. A valid method for calculating a reference range was used. Statistical Tests: Shapiro–Wilk test for normality; Tukey robust approach for identification of outliers; reference range calculation with confidence intervals. Results: Reference ranges for measurement of myocardial T1 were calculated, with confidence intervals, enabling comparison with clinically important differences. At 3 T: 1129 to 1301 msec at site 1 ( n = 21) and 1160 to 1309 msec at site 2 ( n = 59), and at 1.5 T at site 2: 933 to 1020 msec (male, n = 130) and 965 to 1054 msec (female, n = 68). The 3 T reference range from site 1 was successfully benchmarked against the 3 T reference range at site 2. Data Conclusion: Myocardial T1 reference ranges can be properly characterized, enabling clinical comparison to a valid reference range with known confidence intervals, using methodology similar to that described in this report. Level of Evidence: 3 Technical Efficacy Stage: 3 J. Magn. Reson. Imaging 2019;50:771–778.